(untitled) (Fiep Bulletin - online, 2014)
The Piracema Project - Swimming For Carrying People of Special Necessities of the University of Santa Cruz do Sul is realized in partnership with the APAE. When initiating in the project, the participants have to realize a battery of tests somatomotors and, after of 10 months of aquatic intervention, the after-tests are realized. Objective: to verify the evolution in the results of somatomotors tests applied. Method of inquiry: 19 people with age between 5 and 43 years had been subject to this study. In this battery of tests, they applied: flexibility, explosive force of inferior members (horizontal jump) and explosive force of superior members (medicine ball throw). Results: In the flexibility test, 94.74% had increased his indices and 5.26% had kept the same indice of the pre-testing. In relation to the test of the horizontal jump, we verify that 42.1% had improved and 31.58% had reduced the index, 26.32% had not realized the test. In the medicine ball throw, 63.16% had improved his indices, 26.13% had gotten worse in relation to the pre-test . Conclusion: Comparing the pre and pos-test, the results of the tests shown to us that, after the aquatic interference of 10 months, the participants of the Project, in generally, had improved their individual indices.